Bulk‐like Pt(100)‐oriented Ultrathin Surface: Combining the Merits of Single Crystals and Nanoparticles to Boost Oxygen Reduction Reaction. Issue 4 (14th December 2022) - Gong, Shuyan; Sun, Mingze; Lee, Yiyang; Becknell, Nigel; Zhang, Jiangwei; Wang, Zhongqi; Zhang, Liang; Niu, Zhiqiang
Abstract: Single crystal surfaces with highly coordinated sites very often hold high specific activities toward oxygen reduction reaction (ORR) and others. Transposing their high specific activity to practical high‐surface‐area electrocatalysts remains challenging. Here, ultrathin Pt(100) alloy surface is constructed via epitaxial growth. The surface shows 3.1–6.9 % compressive strain and bulk‐like characteristics as demonstrated by site‐probe reactions and different spectroscopies. Its ORR activity exceeds that of bulk Pt3 Ni(100) and Pt(111) and presents a 19‐fold increase in specific activity and a 13‐fold increase in mass activity relative to commercial Pt/C. Moreover, the electrochemically active surface area (ECSA) is increased by 4‐fold compared to traditional thin films (e.g. NSTF), which makes the catalyst more tolerant to voltage loss at high current densities under fuel cell operation. This work broadens the family of extended surface catalysts and highlights the knowledge‐driven approach in the development of advanced electrocatalysts. Abstract : Bulk‐like Pt(100)‐oriented ultrathin surface with up to 6.9 % compressive strain combines the high specific activity of single crystals and high electrochemically active surface area of nanoparticles, achieving order‐of‐magnitude improvement in specific and mass activities toward oxygen reduction reaction compared with benchmark Pt/C.